Progesterone from the cumulus cells is the sperm chemoattractant secreted by the rabbit oocyte cumulus complex. - Héctor Alejandro Guidobaldi; María Eugenia Teves; Diego Rafael Uñates; Agustín Anastasía; Laura Cecilia Giojalas (PLoS ONE, 2008)
Sperm chemotaxis in mammals have been identified towards several female sources as follicular fluid (FF), oviduct fluid, and conditioned medium from the cumulus oophorus (CU) and the oocyte (O). Though several substances were confirmed as sperm chemoattractant, Progesterone (P) seems to be the best chemoattractant candidate, because: 1) spermatozoa express a cell surface P receptor, 2) capacitated spermatozoa are chemotactically attracted in vitro by gradients of low quantities of P; 3) the CU cells produce and secrete P after ovulation; 4) a gradient of P may be kept stable along the CU; and 5) the most probable site for sperm chemotaxis in vivo could be near and/or inside the CU. The aim of this study was to verify whether P is the sperm chemoattractant secreted by the rabbit oocyte-cumulus complex (OCC) in the rabbit, as a mammalian animal model. By means of videomicroscopy and computer image analysis we observed that only the CU are a stable source of sperm attractants. The CU produce and secrete P since the hormone was localized inside these cells by immunocytochemistry and in the conditioned medium by enzyme immunoassay. In addition, rabbit spermatozoa express a cell surface P receptor detected by western blot and localized over the acrosomal region by immunocytochemistry. To confirm that P is the sperm chemoattractant secreted by the CU, the sperm chemotactic response towards the OCC conditioned medium was inhibited by three different approaches: P from the OCC conditioned medium was removed with an anti-P antibody, the attractant gradient of the OCC conditioned medium was disrupted by a P counter gradient, and the sperm P receptor was blocked with a specific antibody. We concluded that only the CU but not the oocyte secretes P, and the latter chemoattract spermatozoa by means of a cell surface receptor. Our findings may be of interest in assisted reproduction procedures in humans, animals of economic importance and endangered species.